Очаг землетрясения как возбудимая среда: теоретические сейсмограммы простейшей оптимальной модели - Костинский, А.С. (Видавничий дім "Академперіодика" НАН України, 2009)
У рамках пiдходу до описання осередку землетрусу з позицiй механiки збудливих середовищ дослiджується отримана автором як результат схеми оптимального конструювання обмежена в часi функцiя стрибка зсуву. Для вiдповiдної “квазiдинамiчної” моделi будуються “наведенi” теоретичнi сейсмограми, аналiзується характер залежностi вiд параметрiв моделi. In the context of an approach to the description of earthquake foci from the positions of excitable medium mechanics, a bounded-in-time displacement discontinuity function obtained by the author as a result of the optimal construction scheme is studied. For the corresponding “quasidynamic” model, “reduced” theoretical seismograms are plotted, and the pattern of the dependence on model parameters is analyzed.